2014
DOI: 10.1007/s11116-014-9534-5
|View full text |Cite
|
Sign up to set email alerts
|

Volatile earmarked revenues and state highway expenditures in the United States

Abstract: Heavy use of transportation-related revenues earmarked for highways is one of the distinguishing characteristics of state highway finance in the United States. This is the first study to examine the potentially differential effects of earmarked revenue volatility on state highway expenditures. Using panel data for over 30 years, I found in both OLS and 2SLS estimations that state highway expenditures did not respond to upward cyclical deviations in earmarked revenues. Also, a one-percentage-point downward devi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 49 publications
(49 reference statements)
0
10
0
Order By: Relevance
“…They should also be orthogonal to the error term because small changes in omitted factors influencing test scores or salaries do not result in a change in the value of rank, although this may not hold true for observations near cross‐over points. However, as in the studies employing this method (Evans and Kessides ; Kroszner and Stratmann ; Globerman and Shapiro ; Nguyen‐Hoang ; Nguyen‐Hoang and Duncombe ), a small number of ranks, and hence cross‐over points, are chosen to reduce this possibility.…”
Section: Empirical Approachmentioning
confidence: 99%
“…They should also be orthogonal to the error term because small changes in omitted factors influencing test scores or salaries do not result in a change in the value of rank, although this may not hold true for observations near cross‐over points. However, as in the studies employing this method (Evans and Kessides ; Kroszner and Stratmann ; Globerman and Shapiro ; Nguyen‐Hoang ; Nguyen‐Hoang and Duncombe ), a small number of ranks, and hence cross‐over points, are chosen to reduce this possibility.…”
Section: Empirical Approachmentioning
confidence: 99%
“…(1995), Gamkhar (2000Gamkhar ( , 2003, Goel and Nelson (2003), and Bruce et al (2007)) have shown that federal highway funding tends to increase state and local highway funding, thus finding evidence of a "fly paper" effect. Nguyen-Hoang (2015) studied the effect that earmarking highway projects had on state highway spending and found that more earmarked projects relative to trend was not correlated with more highway spending. Conversely, a decrease in the number of earmarked projects relative to trend was associated with a decline in state highway funding.…”
Section: Prior Analysis Of Transportation Spending Politicsmentioning
confidence: 99%
“…Following Nguyen-Hoang (2015), in order to control for public highway efficiency, this study incorporates the theoretical elements of highway efficiency (Equation 8) into the public highway outcome model (Equation 7) and develops a full and realistic theoretical model of public highway outcomes. This model better captures the real public highway production process by taking state highway efficiency differences into account.…”
Section: A Full and Realistic Theoretical Model Of Public Highway Outcomesmentioning
confidence: 99%
“…Public choice theorists argue that the use of earmarked taxes for public services generates positive efficiency gains because it enforces a cost-benefit principle and alleviates the freeriding problem (e.g., Brennan & Buchanan, 1978;Buchanan, 1963). Following Goel and Nelson (2003) and Nguyen-Hoang (2015), three different variables are utilized to capture different dimensions of state highway earmarking behavior. The first variable is HwyUserFeeDedication.…”
Section: State Highway Efficiency Variablesmentioning
confidence: 99%